Impact Of System Characteristics On The Usage Of Electronic Healthcare Records Among Jordanian Healthcare Professionals Performance - Almomani, All'a Mohamad Abdelhamid (2024)
Numerous reports highlight Jordan's lagging technology usage compared to other Arab nations and the global average, with a notable research gap in understanding electronic health records usage among healthcare professionals, necessitating an investigation into the factors affecting their usage, especially in the Jordanian public sector. This study extended the theory of planned behaviour by incorporating cognitive and emotional trust factors, with the identified cognitive factors being perceived usefulness, ease of use, facilitating conditions, data confidentiality, data integrity, and data availability. In addition, current study examined the role of emotional trust as a mediator between the cognitive factors of trust and the actual usage of the system. Furthermore, it introduced the concept of healthcare professionals’ performance within the theory of planned behaviour. This quantitative study employed a cross-sectional temporal separation design with the stratified sampling method and targeted healthcare professionals who rely on the electronic health records system in 33 public hospitals affiliated with the Jordanian Ministry of Health. A total of 459 questionnaires were analysed using partial least squares structural equation modelling. The results of this study revealed that emotional trust was the strongest influencer on the use of electronic health records in Jordan. Social factors also influenced the use of the system, while perceived behavioural control had no effect on the usage of the system among Jordanian healthcare professionals.